[PP.32.12] GENDER DIFFERENCES IN URIC ACID AND CARDIOVASCULAR RISK. (September 2016) - Ameijeiras, A. Hermida; Paz, J.E. Lopez; Alende, M.J.; Gonzalez, G. Calvo; Durán, V. Martínez; Montes, A. Pascual; Lopez, I. Rodriguez; Gomez, C. Calvo
Abstract : Objective: The aim of this study was to assess influence of uric acid levels (UA) and nocturnal BP dipping considering gender differences. Design and method: A cross sectional study was conducted among 404 subjects (55% women) with preserved renal function (MDRD > 60 ml/min. without proteinuria). BP was measured by ambulatory monitoring (ABPM) every 20 min between 07:00 am and 23:00 pm and every 30 min at night, along 48 hours with a Spacelabs 90207 device. We analyzed 48h-systolic and 48h-dyastolic mean ambulatory BP (48h-SBP/48h-DBP), 48 h nocturnal SBP/DBP falling. Clinical and biological assessments were performed in order to detect UA and kydney function. Results: The prevalence rates of UA between men were 55.1% (UA < 6 mg/dl) and 44.9% (UA > 6 mg/dL). Women had lower UA (83.8% < 6 mg/dL, compared to 16.2% > 6 mg/dL). Mean value of UA was 5.6 mg/dL among males (Vs 4.8 mg/dL among females; p: 0.000). We found gender differences on several clinical aspects between males and females as waist circumference (104.5 Vs 94.5 cms; p: 0.00), weight (88.2 Vs 73.3 kg; p: 0.00), 48 h SBP (129.8 Vs 126.6 mmHg; p: 0.05), diurnal SBP (134.4 Vs 131.3 mmHg; p: 0.01), nocturnal SBP (120.3 Vs 117.1 mmHg; p: 0.01) and nocturnal DBP (69.3 Vs 67.5 mmHg; p: 0.03). We only found differences in women (not in men) according to UA (lower Vs higher of 6 mg/dL) on SBP falling (11.1 Vs 8.0 mmHg) and DBP falling (16.4 Vs 13.4 mmHg). 58.6% of non dipper women presented UA over 6 mg/dL. UA correlated poorly and inversely with nocturnal SBP falling (r: -0.133; p = 0.039) and DBP falling (r: -0.163; p = 0.011). Conclusions: In a cohort of renal preserved function subjects. uric acid levels are higher in men and those with central obesity. No association between UA and office or ambulatory BP levels was observed independently of gender. Nevertheless, we observed inverse association between nocturnal BP falling and UA only in women. These results may help us to understand the underlying process of increased cardiovascular risk in women with high uric acid.